What if being or becoming information literate were an adventure? - Dahl, Tove I. (Septentrio Conference Series, 2021)
See RECORDING What if we allowed ourselves to rethink what becoming information literate is about, or can be? In this talk, I will take us along paths of thought that allow us to re-imagine what it might mean to become an information literate person. I will draw from my base in several psychological research traditions and years of experience designing curricula and hands-on teaching in both traditional and non-traditional learning environments. I invite you to join me in thinking about how we might build on what you already do well in IL education by entertaining one simple question: What if being or becoming information literate were an adventure? Where might that take us?